2014
DOI: 10.1016/j.devcel.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Cell Intrinsic Modulation of Wnt Signaling Controls Neuroblast Migration in C. elegans

Abstract: Members of the Wnt family of secreted signaling proteins are key regulators of cell migration and axon guidance. In the nematode C. elegans, the migration of the QR neuroblast descendants requires multiple Wnt ligands and receptors. We found that the migration of the QR descendants is divided into three sequential phases that are each mediated by a distinct Wnt signaling mechanism. Importantly, the transition from the first to the second phase, which is the main determinant of the final position of the QR desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
122
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(131 citation statements)
references
References 45 publications
7
122
0
Order By: Relevance
“…This hypothesis is consistent with previous observations that pyramidal precursors in the developing cortex express not only Wnt5A but also the non-canonical receptors Ror 1 and 2 (Endo et al, 2012). Intriguingly, a similar cell-intrinsic modulation of Wnt canonical as well as non-canonical signaling has been implicated in the control of neuroblast migration in C. elegans (Mentink et al, 2014), indicating that this regulatory mechanism, similarly to guidance by Wnt morphogenic gradient, is evolutionarily conserved. How Wnt5A expression is regulated remains to be determined.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This hypothesis is consistent with previous observations that pyramidal precursors in the developing cortex express not only Wnt5A but also the non-canonical receptors Ror 1 and 2 (Endo et al, 2012). Intriguingly, a similar cell-intrinsic modulation of Wnt canonical as well as non-canonical signaling has been implicated in the control of neuroblast migration in C. elegans (Mentink et al, 2014), indicating that this regulatory mechanism, similarly to guidance by Wnt morphogenic gradient, is evolutionarily conserved. How Wnt5A expression is regulated remains to be determined.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, Wnt signaling has been implicated in dendritic development and synapse formation of cortical neurons in culture (Dickins and Salinas, 2013). Evidence indicates that Wnt proteins guide cell migration and that multiple Wnt ligands and receptors directly regulate cell polarity and motility in a variety of vertebrate and invertebrate systems (Lyuksyutova et al, 2003;Witze et al, 2008;Mentink et al, 2014). Whether there is a similar direct role of Wnt signaling in regulating neuronal migration in the mammalian cerebral cortex remains largely unexplored.…”
Section: Introductionmentioning
confidence: 98%
“…Loss of Wnt signaling inhibits neuroblast migration, neural differentiation, and suppression of the development of the forebrain. [35][36][37][38] Moreover, we previously reported that mutations in b-catenin contribute to ID in humans, 39,40 and mutations in d-catenin, some of which abrogate its biochemical interaction with b-catenin, can contribute to severe autism in females, 32 strengthening further the link between Wnt signaling and human neurodevelopmental disorders.…”
mentioning
confidence: 96%
“…The Wnt/β-catenin pathway has been intensively studied in C. elegans, with a significant focus on Wnt-guided cell migration and the SYS-1/POP-1 Wnt asymmetry pathway, required for proper fate of seam cells and some neurons, while the role of BAR-1 in the Pn.p cells has remained less characterized (Eisenmann et al, 1998;Gleason et al, 2002;Harterink et al, 2011;Korswagen, 2002;Lin et al, 1998;Maloof et al, 1999;Mentink et al, 2014;Mila et al, 2015;Park and Priess, 2003;Shetty et al, 2005;Whangbo and Kenyon, 1999). While genetic evidence shows that β-catenin/BAR-1 is an inhibitor of the eff-1 gene, it is conventionally known to act as a transcriptional co-activator with the TCF/POP-1 protein, suggesting that the effect BAR-1 has on eff-1 is through another intermediate protein.…”
Section: Discussionmentioning
confidence: 99%